A Tool for Performing Automatic Kinematic Analysis on Rock Outcrops - Taboni, Battista; Tagliaferri, Iuri Dino; Umili, Gessica (Geosciences (Basel), 2022)
The assessment of rock outcrops’ predisposition to the main possible kinematisms represents the preliminary step of stability analysis: Markland’s tests for sliding and toppling constitute a milestone due to the ease of use and interpretation of results. Orientation and friction angles of the main discontinuity sets and orientation of rock faces are required as input to perform the test on a stereonet graphically. However, for natural outcrops, the orientation of rock faces could vary significantly, and the test should be performed assuming all the representative ones. To speed up this process, the authors set up an automatic procedure based on the GIS environment working principles and developed it in Matlab language. Main discontinuity sets orientation and relative friction angles, along with slope and aspect data representing the rockface orientation of the considered outcrop, are the input data. The slope and aspect data are in GeoTIFF format, the most common format for georeferenced raster files employed in a GIS environment. The Matlab code performs Markland’s tests for planar and wedge sliding and flexural toppling, considering all the possible sets or intersections of sets, and provides the output with the same extent and georeferencing of the input data. The outputs are a series of GeoTIFF raster files describing the result for each kinematism separately and globally, which can be imported directly into GIS. The global results can also be used to map source areas for 3D rockfall numerical simulations. The code was validated through a case study by comparing its results with those obtained by performing the conventional tests singularly on a number of significant rock faces. The results obtained in the case study show that the algorithm produces reliable results consistent with those provided by traditional methods.